A Cost-Efficient Software Based Router and Traffic Generator for Simulation and Testing of IP Network - Jun, Su; Przystupa, Krzysztof; Beshley, Mykola; Kochan, Orest; Beshley, Halyna; Klymash, Mykhailo; Wang, Jinfei; Pieniak, Daniel (Electronics (Basel), 2020)
The development was carried out using the Qt5.2 integrated development environment, which uses the programming language C++. The main advantage of this environment is that the code written in it can be compiled to different platforms (for example, Windows, Linux, Mac OS). A software router based on a modular architecture has been developed. It uses the socket technology, which allows forming a program-oriented packet network with any topology, including full-coupled topology. A network traffic generator to test the developed software router has been designed. We proposed a scheme to measure the packet processing time of a router using a specialized packet-capture network interface cards (NIC 1 and NIC 2) and a novel traffic generator installed on PC. Based on an experimental test bed we confirmed that our software router provides a cost-efficient alternative to the expensive, special hardware router CISCO 2801.